Exclusive Inclusivity on The Disabled Individuals in Beauty Product Ads: A Case Study of Pond's Indonesia Campaign "Wajahmu Kekuatanmu” - Intan Fitranisa; Mytha Eliva Veritasia (ULTIMA Comm, 2024)
This paper attempts to investigate the meaning of inclusivity in Pond's Indonesia Ads: "Wajahmu Kekuatanmu” which features Greesella Adhalia, member of Indonesian Pop Group JKT48 and disability influencer Kirana Salsabila. Using discourse analysis, this paper concludes that instead of promoting disability and inclusivity, Pond's Indonesia: "Wajahmu Kekuatanmu” asserts that to exist and be able to empower others, one must embrace the social standard of ideal beauty and eliminate their "disabled-ness”. Inclusivity is therefore reduced to the symbolic annihilation of a certain register of an individual, in this case Kirana's deaf and speech impairment, as the campaign exclusively suggests it does not matter what she lacks, her face is a significant mark of opportunity and hope. As a result, rather than her disability that others might find empowering, it is that glistening and flawless face which people, especially young girls, inspire and aspire to possess. Keywords: Ads, Beauty Products, Disability, Inclusivity, Social Equality